Silica and Its Antagonistic Effects on Transforming Growth Factor-β in Lung Fibroblast Extracellular Matrix Production. (1st March 2001) - Baroni, Tiziano; Bodo, Maria; D'Alessandro, Alessandra; Conte, Carmela; Calvitti, Mario; Muzi, Giacomo; Lumare, Alessandro; Bellocchio, Silvia; Abbritti, Giuseppe
Abstract : Background: Silicosis, a pneumoconiosis marked by interstitial pulmonary fibrosis, is caused by inhalation of free crystalline silica particles. When silica particles are injected into the lower lung, they are translocated across the epithelium into the interstitial space, where macrophage-derived growth factors affect lung fibroblast proliferation and collagen deposition. We hypothesized that silica may act directly on pulmonary fibroblasts modifying extracellular matrix (ECM) synthesis and that the effects of silica may be mediated by transforming growth factor-β (TGFβ) overproduction. Methods: To test this hypothesis, we studied a human lung fibroblast cell line (WI-1003) exposed to silica in vitro. We investigated cell morphology by electron microscopic procedure, cell growth, collagen production, and glycosaminoglycans (GAG) composition by radiolabeled precursors. Cytokine and growth factor synthesis were evaluated by specific enzyme-linked immunoadsorbent assay kits and Northern blotting analysis. Results: Pulmonary fibroblasts internalized silica particles without detectable cell damage. Silica directly stimulated collagen synthesis and decreased the amount of 3 H-glucosamine-labeled GAG. Silica-treated fibroblasts secreted less TGFβ than untreated controls, antagonized the stimulatory effect of TGFβ on ECM synthesis, and reversed TGFβ-induced inhibition of cell proliferation. Northern blotting analysis showed increased interleukin-1α (IL-1α) mRNA after silica treatment. IL-1α had no influence on collagen synthesis but increased the number of WI-1003 fibroblasts. Conclusions: These results support our hypothesis that lung fibroblasts are direct silica targets. However, contradicting our hypothesis, silica antagonized TGFβ activities through a TGFβ downregulation and an IL-1α upregulation. The complex pattern of TGFβ and IL-1α regulation in pulmonary fibroblasts is imbalanced by silica exposure and might play a key role in silica-mediated pulmonary fibrosis.